Simulation Studies on Image Reconstruction Algorithm for Portable Electrical Capacitance Tomography - Abdul Rahim, Ruzairi; Hamzah, Ahmad Azahari; Mohamad, Elmy Johana; Pusppanathan, Jaysuman; Abdul Kadir, Kushsairy; Mohamad Ameran, Hanis Liyana (International Journal of Integrated Engineering, 2018)
Electrical capacitance tomography (ECT) is a non-invasive and non-intrusive internal visualization tomographic modality which promising a better quantification by providing cross-sectional distribution information of any kind of multiphase flow. These studies aim to investigate the non-iterative and iterative image reconstruction for 16 channels of portable electrical capacitance tomography (ECT) through simulation work. Linear Back Projection (LBP) as a non-iterative algorithm was compared with the Landweber and generalized vector sampled pattern matching (GVSPM) iterative algorithm for four cases which are core flow, annular flow, stratified flow and two circles by evaluation of image error and image correlation. The results show Landweber algorithms produces lowest percentage error, close to phantom as higher correlation coefficient and acceptable elapsed time. Iterative image reconstruction will produce accurate results by eliminating the artifacts near actual object and enhance the capability of segmented ECT in multiphase flow identification.